Fecal microbiota transplantation to prevent acute graft-versus-host disease: pre-planned interim analysis of donor effect - Swetha Reddi; Liliia Senyshyn; Maryam Ebadi; Daniel Podlesny; Samuel S. Minot; Ted Gooley; Amanda J. Kabage; Geoffrey R. Hill; Stephanie J. Lee; Alexander Khoruts; Armin Rashidi (Nature Communications)
Abstract Gut microbiota disruptions after allogeneic hematopoietic cell transplantation (alloHCT) are associated with increased risk of acute graft-versus-host disease (aGVHD). We designed a randomized, double-blind placebo-controlled trial to test whether healthy-donor fecal microbiota transplantation (FMT) early after alloHCT reduces the incidence of severe aGVHD. Here, we report the results from the single-arm run-in phase which identified the best of 3 stool donors for the randomized phase. The primary and key secondary endpoints were microbiota engraftment and severe aGVHD, respectively. Three cohorts of patients (20 total) received FMT, each from a different donor. FMT was safe and effective in restoring microbiota diversity and commensal species. Microbiota engraftment, determined from shotgun sequencing data, correlated with larger microbiota compositional shifts toward donor and better clinical outcomes. Donor 3 yielded a median engraftment rate of 66%, higher than donors 1 (P = 0.02) and 2 (P = 0.03) in multivariable analysis. Three patients developed severe aGVHD; all 3 had received FMT from donor 1. Donor 3 was selected as the sole donor for the randomized phase. Our findings suggest a clinically relevant donor effect and demonstrate feasibility of evidence-based donor selection. FMT is a holistic microbiota restoration approach that can be performed as a precision therapeutic. ClinicalTrials.gov identifier NCT06026371